In-situ utilization of membrane foulants (FeOx+MnOx) for the efficient membrane cleaning. (15th February 2022) - Li, Boda; Ma, Jun; Qiu, Wei; Li, Wenqian; Zhang, Bin; Ding, An; He, Xu
Highlights: In-situ generated FeOx and MnOx are used for membrane cleaning. Flux recovery could be higher than 95% by the proposed method. Efficient membrane cleaning are achieved by low H2 O2 dosage and short time. PAC is a key factor for MnOx removal and membrane cleaning. Abstract: Preoxidation-ultrafiltration process is an effective method for Fe 2+ and Mn 2+ removal, in which Fe 2+ (Mn 2+ ) are firstly oxidized to FeOx (MnOx ), then collected by the ultrafiltration membrane. However, the simultaneous presence of Fe 2+, Mn 2+, and organics in feed can cause severe membrane fouling, which inhibits the overall performance of this method prominently. In this study, a novel FeOx +MnOx +H2 O2 membrane cleaning method is proposed based on the idea of turning in-situ generated membrane foulants, i.e., FeOx +MnOx, into the catalysts for membrane cleaning. The results demonstrate that the FeOx +MnOx +H2 O2 system can achieve more than 95% membrane flux recovery and remove almost all irreversible membrane foulants within only 5 min and with only 0.5 % w t % H2 O2 solution. The outstanding performance of the system is mainly attributed to the catalytic decomposition of H2 O2 to generate both highly reactive radicals, such as hydroxyl radicals (·OH), and abundant oxygen. In addition, when the membrane is loaded by only MnOx, polyaluminium chloride (PAC) as the coagulator demonstrates prominent influence on the performance of membrane cleaning. However, PAC makes almost no contribution to membrane cleaning when the membrane is loaded by FeOx . This is because coagulation induced by PAC exerts more prominent impact on the particle size distribution of MnOx than that of FeOx . In conclusion, the catalytic decomposition of H2 O2 by in-situ generated FeOx +MnOx is a promising advanced oxidation process to achieve outstanding membrane cleaning performance under the condition of low H2 O2 concentration and no extra dosage of catalysts. The novel membrane cleaning system exhibits high potential for the practical membrane treatment processes to treat water with high contents of Fe and Mn. Graphical abstract: Image, graphical abstract